Pengaruh Motivasi Hedonik, Faktor Sosial dan Resiko Terhadap Pembayaran Langsung Uang Elektronik Pada Pengguna E-Commerce Shopee - Fitria, Dilla; Lubis, Abdul Rahman (Manajemen Inovasi Bisnis dan Strategi, 2024)
This research aims to determine the influence of hedonic motivation, social factors and risk on direct electronic money payments for Shopee e-commerce users. The sample used in this research was Shopee e-commerce users in Banda Aceh City, totaling 200 respondents. The data collection equipment used in this research is a questionnaire. The sampling technique used was non-probability sampling with the type used being purposive sampling. Structural Equation Modeling (SEM) is used as an analysis method to determine the influence of the variables involved. Based on the results of SEM analysis, it shows that hedonic motivation influences payment habits, social factors influence payment habits, risk influences payment habits, payment habits influence behavioral intentions towards electronic money, hedonic motivation influences behavioral intentions towards electronic money, social factors influence behavioral intentions towards electronic money, risk has no effect on behavioral intentions towards electronic money, payment habits partially mediate the influence of hedonic motivation on behavioral intentions towards electronic money, payment habits partially mediate the influence of social factors on behavioral intentions towards electronic money, payment habits partially mediate partial influence of risk on behavioral intentions towards electronic money.